Pengetahuan Ibu Hamil Tentang Akupresur di Puskesmas Margodadi: Knowledge of Pregnant Women About Acupressure at Margodadi Health Center - Neni Setianingsih; Widayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2021)
Changes during pregnancy often cause discomfort in pregnant women, discomfort that is often experienced in the form of nausea, vomiting, migraines, difficulty sleeping and back pain. Acupressure in pregnancy is a non-pharmacological therapy that can be used to treat the discomfort of pregnant women. Descriptive quantitative research. The method used cross sectional approach. The population of this study were all pregnant women at Margodadi Health Center in November 2020 with total of 63 mothers. The sampling technique was total sampling and used Univariate analysis. Describe the knowledge of pregnant women about acupressure, the definition of acupressure, the benefits of acupressure, acupressure contraindications, how to do acupressure, and acupressure points that can be used in pregnancy. The results of the univariate analysis, most of the respondents had less knowledge about the understanding of 51 respondents (51.0%), less knowledgeable about the benefits of 49 respondents (77.8%), less knowledgeable about contraindications 52 (82.5%), less knowledgeable about how to do 40 (63.5%), less knowledge about acupressure points that can be done in pregnancy 35 (55.6%), and less knowledge about acupressure knowledge 51 (81.0%). Most of the pregnant women lacked knowledge of acupressure knowledge 51 (81.0%). Most of the pregnant women lacked knowledge of acupressure knowledge 51 (81.0%). It is expected that pregnant women seek information about acupressure in pregnancy from the midwife. And hope for midwives, should be able to attend seminars and training on acupressure in pregnancy. ABSTRAK Perubahan selama kehamilan seringkali menyebabkan ketidaknyaman pada ibu hamil seperti mual muntah, migrain, sulit tidur dan nyeri punggung. Akupresur pada kehamilan merupakan terapi non farmakologi yang digunakan untuk mengatasi ketidaknyaman ibu hamil. Penelitian deskriptif kuantitatif, metode pendekatan cross sectional. Populasi dari penelitin ini adalah seluruh ibu hamil di Puskesmas Margodadi bulan November 2020 dengan jumlah 63 ibu hamil. Teknik pengambilan sampel adalah total sampling dan analisis yang digunakan analisis univariat Mendeskripsikan pengetahuan ibu hamil tentang akupresur, pengertian akupresur, manfaat akupresur, kontraindikasi akupresur, cara melakukan akupresur, dan titik-titik akupresur yang dapat dilakukan pada kehamilan. sebagian besar responden berpengetahuan kurang bepengetahuan kurang tentang pengetahuan akupresur 51 (81,0%), berpengetahuan kurang tentang pengertian 51 responden (51,0%), berpengetahuan kurang tentang manfaat 49 responden (77,8%), berpengetahuan kurang tentang kontraindikasi 52 (82,5%), berpengetahuan kurang tentang cara melakukan 40 (63,5%), dan bepengetahuan kurang tentang titik-titik akupresur yang dapat dilakukan pada kehamilan 35 (55,6%). Sebagian besar ibu hamil dalam pengetahuan kurang tentang pengetahuan akupresur 51 (81,0%). Diharapkan ibu hamil mencari informasi tentang akupresur pada kehamilan dari Bidan. Dan harapan untuk Bidan, hendaknya dapat mengikuti seminar dan pelatihan tentang akupresur pada kehamilan.